Impact Of Returns, Risk On Interest In Investing During The Covid-19 Pandemic - Darman, Darman Saputra; Julia, Julia (CV. Inara, 2021)
This study aims to determine the effect of return, risk on interest in investing during the covid 19 pandemic. The population in this study were all customers of the Indonesia Stock Exchange (IDX) Pangkalpinang City with a total sample of 377 respondents. The sampling technique was carried out using a non-probability sampling method, namely the accidental sampling technique. This type of research is quantitative research with primary data types obtained directly through the distribution of online questionnaires using google form. This research uses multiple regression analysis technique.The results of this study indicate that (1) the return variable has a significant effect on interest in investing during the covid 19 pandemic. (2) the risk variable has a significant effect on interest in investing during the covid 19 pandemic. (3) the attitude variable has a significant effect on interest in investing during the pandemic. covid 19. The conclusion of this study shows that IDX customers have a good understanding of returns and risks, and have a positive attitude towards investing during the covid 19 pandemic, encouragement from those closest to them as well as the confidence from within customers to invest, greatly affects customer investment interest during the covid 19 pandemic.